Functional Amyloid Signaling via the Inflammasome, Necrosome, and Signalosome: New Therapeutic Targets in Heart Failure - Parry, Traci L.; Melehani, Jason H.; Ranek, Mark J.; Willis, Monte S. (Frontiers in Cardiovascular Medicine, 2015)
As the most common cause of death and disability globally, heart disease remains an incompletely understood enigma. A growing number of cardiac diseases are being characterized by the presence of misfolded proteins underlying their pathophysiology, including cardiac amyloidosis and dilated cardiomyopathy (DCM). At least nine precursor proteins have been implicated in the development of cardiac amyloidosis, most commonly caused by multiple myeloma (MM) light chain disease and disease-causing mutant or wildtype transthyretin (TTR). Similarly aggregates with PSEN1 and COFILIN-2 have been identified in up to 1/3 of idiopathic DCM cases studied indicating the potential predominance of misfolded proteins in heart failure. In this review, we present recent evidence linking misfolded proteins mechanistically with heart failure and present multiple lines of new therapeutic approaches that target the prevention of misfolded proteins in cardiac TTR amyloid disease. These include multiple small molecule pharmacological chaperones now in clinical trials designed specifically to support TTR folding by rational design, such as tafamidis, and chaperones previously developed for other purposes, such as doxycycline and tauroursodeoxycholic acid. Lastly, we present newly discovered non-pathological “functional” amyloid structures, such as the inflammasome and necrosome signaling complexes, which can be activated directly by amyloid. These may represent future targets to successfully attenuate amyloid-induced proteotoxicity in heart failure as the inflammasome, for example, is being therapeutically inhibited experimentally in autoimmune disease. Together, these studies demonstrate multiple novel points in which new therapies may be used to primarily prevent misfolded proteins or to inhibit their downstream amyloid-mediated effectors, such as the inflammasome, to prevent proteotoxicity in heart failure.